Saturated and unsaturated stability analysis of slope subjected to rainfall infiltration - Nurly Gofar (2018)
This paper presents results of saturated and unsaturated stability analysis of typical residual slopes subjected to rainfall infiltration corresponds to 50 years rainfall return period. The slope angles considered were 45° and 70°. The saturated stability analyses were carried out for original and critical ground water level commonly considered by practicing engineer. The analyses were conducted using limit equilibrium method. Unsaturated stability analyses used combination of coupled stress–pore-water pressure analysis to evaluate the effect of rainfall infiltration on the deformation and transient pore-water pressure on slope stability. Slope stability analyses were performed at some times during and after rainfall infiltration. Results show that the critical condition for slope made by sandy material was at the end of rainfall while for clayey material was at some specified times after the rainfall ceased. Unsaturated stability analysis on sandy soil gives higher factor of safety because the soil never reached saturation. Transient analysis using unsaturated soil concept could predict more critical condition of delayed failure of slopes made up of clayey soil.